Systematic review of anorectal varices. (December 2013) - Maslekar, S.; Toh, E.‐W.; Adair, R.; Bate, J. P.; Botterill, I.
Abstract Aim Anorectal varices are an uncommon, but significant, source of bleeding in patients with portal hypertension. The aim of this article was to review systematically the available literature on the aetiology, clinical presentation and management of anorectal varices, and to suggest a simple treatment algorithm based on available evidence and local expertise. Method A systematic literature search was carried out to identify articles on anorectal varices, and the search strategy identified 57 relevant references. The inclusion criteria included a consecutive cohort of patients having treatment for anorectal varices with details of success rates and the number of different techniques used. Exclusion criteria included papers published in languages other than English with no English version and results not reported separately for anorectal varices. Results Anorectal varices can occur in up to 89% of patients with portal hypertension, although the overall incidence in the general population is low. Diagnosis is best achieved with anoscopy or flexible sigmoidoscopy. The current evidence supports the use of local procedures, such as endoscopic band ligation, to arrest bleeding where feasible, with radiological or surgical procedures used in the event of failure. Conclusion As there are no large series on this pathology, we present a systematic approach for the patient with anorectal varices.